BH3 Mimetics in Hematologic Malignancies - Klener, Pavel; Sovilj, Dana; Renesova, Nicol; Andera, Ladislav (International journal of molecular sciences, 2021)
Hematologic malignancies (HM) comprise diverse cancers of lymphoid and myeloid origin, including lymphomas (approx. 40%), chronic lymphocytic leukemia (CLL, approx. 15%), multiple myeloma (MM, approx. 15%), acute myeloid leukemia (AML, approx. 10%), and many other diseases. Despite considerable improvement in treatment options and survival parameters in the new millennium, many patients with HM still develop chemotherapy‑refractory diseases and require re-treatment. Because frontline therapies for the majority of HM (except for CLL) are still largely based on classical cytostatics, the relapses are often associated with defects in DNA damage response (DDR) pathways and anti-apoptotic blocks exemplified, respectively, by mutations or deletion of the TP53 tumor suppressor, and overexpression of anti-apoptotic proteins of the B-cell lymphoma 2 (BCL2) family. BCL2 homology 3 (BH3) mimetics represent a novel class of pro-apoptotic anti-cancer agents with a unique mode of action-direct targeting of mitochondria independently of TP53 gene aberrations. Consequently, BH3 mimetics can effectively eliminate even non-dividing malignant cells with adverse molecular cytogenetic alterations. Venetoclax, the nanomolar inhibitor of BCL2 anti-apoptotic protein has been approved for the therapy of CLL and AML. Numerous venetoclax-based combinatorial treatment regimens, next-generation BCL2 inhibitors, and myeloid cell leukemia 1 (MCL1) protein inhibitors, which are another class of BH3 mimetics with promising preclinical results, are currently being tested in several clinical trials in patients with diverse HM. These pivotal trials will soon answer critical questions and concerns about these innovative agents regarding not only their anti-tumor efficacy but also potential side effects, recommended dosages, and the optimal length of therapy as well as identification of reliable biomarkers of sensitivity or resistance. Effective harnessing of the full therapeutic potential of BH3 mimetics is a critical mission as it may directly translate into better management of the aggressive forms of HM and could lead to significantly improved survival parameters and quality of life in patients with urgent medical needs.
Keywords: Bridged Bicyclo Compounds, Heterocyclic; venetoclax; bicyklické sloučeniny heterocyklické; Humans; Hematologic Neoplasms; biomarkers; nádorový supresorový protein p53; targeted therapy; sulfonamidy; lidé; Biomarkers; hematologic malignancies; zvířata; apoptosis; hematologické nádory; apoptóza; BH3 mimetics; biologické markery; poškození DNA; DNA Damage; Animals; resistance; Apoptosis; Sulfonamides; Tumor Suppressor Protein p53